2015
DOI: 10.1007/s10068-015-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory properties of Chinese ilicifolius vegetable (Acanthopanax trifoliatus (L) Merr) and its reference compounds

Abstract: Stems and leaves of Acanthopanax trifoliatus (L) Merr (AT) are commonly used as an edible vegetable in China. The scientific basis of antioxidant and antiinflammatory activities of AT was investigated. The polyphenol contents and free radical scavenging activities of AT ethanol extracts (EAT) were determined. Chlorogenic acid, isochlorogenic acid A, isochlorogenic acid C, and rutin were identified as major components in EAT. LPS-induced NO production in RAW264.7 cells was decreased significantly (p<0.05) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…After analysis of monguba seeds, 21 phenolic compounds were quantified, among other, higher levels in the phenolic acids, such as 2,5-dihydroxybenzoic acid, caffeic acid, ferulic acid gallic acid, homogentisic acid, p-coumaric acid, and especially chlorogenic acid. Chlorogenic acid is compound derived from caffeic acid and it exhibits several beneficial biological properties, including antibacterial, antiphlogistic, antiviral, and inhibitory effects on carcinogenesis in the large intestine and liver [59,60]. The chlorogenic acid values found in our study were higher than those contents reported for Gordon et al [61] in açaí pulp (0.2 to 16.4 μg/g dry basis).…”
Section: Sift Deskcontrasting
confidence: 73%
“…After analysis of monguba seeds, 21 phenolic compounds were quantified, among other, higher levels in the phenolic acids, such as 2,5-dihydroxybenzoic acid, caffeic acid, ferulic acid gallic acid, homogentisic acid, p-coumaric acid, and especially chlorogenic acid. Chlorogenic acid is compound derived from caffeic acid and it exhibits several beneficial biological properties, including antibacterial, antiphlogistic, antiviral, and inhibitory effects on carcinogenesis in the large intestine and liver [59,60]. The chlorogenic acid values found in our study were higher than those contents reported for Gordon et al [61] in açaí pulp (0.2 to 16.4 μg/g dry basis).…”
Section: Sift Deskcontrasting
confidence: 73%
“…Chlorogenic acid is widely distributed in fruits, having several beneficial biological properties, including antibacterial, antiphlogistic, antiviral, and inhibitory effects on carcinogenesis in the large intestine and liver. [40,41] Studies by Pingret et al [42] and Hao et al [41] have shown that apple contains considerable amounts of hydroxycinnamic acid derivatives which are represented mainly by chlorogenic acid. Hydroxycinnamic acids are generally found primarily esterified with small molecules, as well as bound to cell wall structural components, such as cellulose, lignin and proteins, through ester bonds.…”
Section: Determination Of Bioactive Compounds By Spectrophotometrymentioning
confidence: 99%
“…It has been used as both traditional plant food and medicinal plant. [ 1 2 3 4 5 6 ] As plant food, people of Thailand consume Phak-pam as a vegetable. As a medicinal plant, Phak-pam has been reported as ginseng-like plant.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] It also possessed pharmacological effects, for instance, anti-inflammatory, antioxidant, and anticancer properties. [ 1 2 3 4 5 6 ] Plant food provides nutrients that help maintain the body functions. Nowadays, nutritional information is increasingly concern for many reasons, for example, to meet nutritional requirements or to prevent nutritional deficiency disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation